Mathematical Modelling of Thin Layer Drying of Alfalfa (Medicago sativa L.) Varieties at Different Temperatures - Taşova, Muhammed; Polatcı, Hakan; Özkurt, Mahir (Turkish Journal of Agriculture - Food Science and Technology, 2020)
In this study, the average drying times of the Frigos, Bilensoy, Nimet and Prosementi alfalfa varieties were determined by drying in a convective dryer (50, 60 and 70Â°C) and in the open (sun). In addition, the most suitable thin layer drying models were determined, which are important in controlling the drying processes and developing new product-specific dryers. In drying processes, the moisture content of the product was dried up to 10% compared to the wet base. The first moisture contents of the specified varieties according to the wet base are respectively; 76.20, 75.88, 76.13 and 75.07%. In drying processes, it was determined that drying method and temperatures changed average drying times. The longest drying times were determined in the Frigos variety, which was laid in the sun and dried. When the Frigos variety was dried in the oven at 50, 60 and 70Â°C, the average drying times were determined as 11, 10 and 6 hours. Time-dependent moisture ratios were determined, processed in thin layer drying models and the mathematical model that best predicts drying curves was determined. While creating curves, Page, Midilli, Yağcıoğlu models were used. While acceptable reliability values were found as in all models, among the models, the highest stability value (R2) was found by Midilli was found in equality.